GENERATION Z’s PERCEPTION OF JAVANESE ORAL TRADITION OF MYTH AND TABOO ORA ILOK IN JAVANESE SOCIETY - Nur Fitria, Tira (UI Scholars Hub, 2023)
The various myth and taboos of ora ilok are familiar among several Javanese groups. The objective of this research is to understand generation Z’s perception of the Javanese myth and taboo ora ilok in Javanese society. This research employs the descriptive qualitative method, involving 76 respondents from various regions of Java such as Central Java, East Java, West Java, and the Special Region of Yogyakarta. The respondents were born between 1996 and 2005. Results show that the majority of respondents do not believe in the ora ilok myths. However, there is a different opinion from Generation Z. Some consider myths as a joke and treat them with scepticism, while a few still believe in these myths, viewing them as rules that must be followed, with potential repercussions for breaking them. Meanwhile, none of the respondents believes in the ora ilok taboo. Ora ilok is a Javanese term used to describe something which is not good and unethical due to its associated prohibitions. It is unwritten and serves as important rules of politeness, serving as a reminder for children, teenagers, and adults. There are values behind the word ora ilok, but the elders usually emphasize its negative consequences on the physical and mental well-being of those who violate these rules. This serves as a reminder for the Javanese to behave politely and respect the rights of others. However, there is a difference in the judgment of generation Z. Many of them no longer believe in ora ilok, while some view it as a joke and treat it with scepticism. However, these myths and taboos are gradually eroding in the new culture of this era.